The Canadian Reconciliation Barometer: a rigorous tool for tracking reconciliation in Canada - Starzyk, K. B.; Neufeld, K. H. S.; Efimoff, I. H.; Fontaine, A. S. M.; White, E. E.-L.; Moran, R.; Peachey, D.; Fontaine, L. S.; Welch, M. A. (Frontiers in Social Psychology, 2024)
In this manuscript, we discuss the development, psychometric validation, and implications of the 64item, 13-indicator self-report Canadian Reconciliation Barometer. After briefly describing the context, our team, our grounding in Indigenous perspectives, and consultation processes, we outline our rigorous process of item development through two nationally representative studies of participants living in Canada (Study 1: 582 Indigenous and 994 non-Indigenous participants; Study 2: 537 Indigenous and 1,112 non-Indigenous participants). We conclude by discussing how our development process and results contribute to conceptualizations of reconciliation, as well as how to use the Canadian Reconciliation Barometer for social change.